A randomized crossover study investigating the running economy of highly-trained male and female distance runners in marathon racing shoes versus track spikes - Barnes, K. R.; Kilding, A. E. (Sports Medicine, 2019)
Background: Running economy represents a complex interplay of physiological and biomechanical factors that are able to adapt chronically through training, or acutely through other interventions such as changes in footwear. The Nike Vaporfly (NVF) shoe was designed for marathon running on the roads and has been shown to improve running economy by ~ 4% compared with other marathon shoes, however, during track racing, distance runners traditionally wear a much lighter shoe with an embedded spike plate around the forefoot. Objective: The aim of this study was to determine if, and to what extent, the NVF shoes improve running economy compared with established track spikes (Nike Zoom Matumbo 3 [NZM]) and marathon racing shoes (Adidas Adizero Adios 3 [ADI]). Methods: Twenty-four highly-trained runners (12 male, 12 female) ran 4 × 5 min trials on a treadmill while wearing each of the four shoe conditions: NVF, NZM, ADI, and the NVF matched in weight to the ADI shoe (NVF +), during three separate visits—visit 1: familiarization; visit 2: 14 and 18 km·h-1 for men, 14 and 16 km·h-1 for women; visit 3: 16 km·h-1 for men, 15 km·h-1 for women, plus a maximal rate of oxygen uptake (VO2max) test for both sexes. We measured the rates of oxygen uptake (VO2), carbon dioxide production and biomechanical measures while running at each velocity and shoe condition. Results: The NVF shoe improved running economy by 2.6 ± 1.3% compared with the NZM, 4.2 ± 1.2% compared with ADI, and 2.9 ± 1.3% when matched in weight of the ADI shoe. Among the 24 subjects, the difference in running economy over the four velocities between the NVF and NZM shoes ranged from + 0.50 to - 5.34%, and - 1.72 to - 7.15% for NVF versus ADI. Correlations between changes in running economy and changes in biomechanical variables were either trivial or small, but unclear. Conclusion: The NVF enhanced running economy compared with track spikes and marathon shoes, and should be considered a viable shoe option for track and road racing.